In Silico Analysis of Immunogenic Epitopes in the VP2 Protein of Canine Parvovirus and Codon Optimization for Multivalent Vaccine Design - Hossein Samiei-Abianeh; Mahdi Tat; Masoumeh Bolandian; Seyed Akbar Arianzad; Jafar Salimian (Iranian South Medical Journal, 2025)
Background: Canine parvovirus (CPV) is one of the major agents of severe viral gastroenteritis in dogs. Although vaccines are available, the emergence of new serotypes and mutations in the VP2 protein can compromise vaccine efficacy. Therefore, identifying both conserved and serotype-specific immunogenic regions is crucial for the design of recombinant vaccines. This study aimed to design and optimize a recombinant vaccine based on conserved immunogenic regions of the VP2 protein from different CPV serotypes. Materials and Methods: Amino acid sequences of the VP2 protein from four CPV serotypes were retrieved from the NCBI database and aligned using Clustal Omega. Structural and immunological features were analyzed using tools such as SignalP, TOPOCONS, and DIpro. Protein solubility, secondary and tertiary structures, and physicochemical properties were evaluated using Protein-Sol, I-TASSER, and ProtParam. The coding sequences were optimized for expression in E. coli and the mRNA secondary structure was analyzed using MFOLD. Results: Multiple sequence alignment identified five key amino acid differences in the 285–450 region of VP2. Tertiary structure analysis showed that this region forms two surface-exposed loops, with the mutated residues at positions 297 and 426 located at the tips. Deletion of the first 20 amino acids improved structural stability, lowering the instability index to 29. Codon optimization increased CAI value to 0.79 and decreased mRNA free energy to –597 kcal/mol. Conclusion: A chimeric recombinant vaccine targeting the 285–450 region of the VP2 protein across  CPV serotypes shows promise as a candidate for broad-spectrum protection. Despite in silico results, experimental validation of protein expression and immune response in animal models is essential.